The social value of pharmaceutical interventions, the Portuguese contribution to sustainable development - Costa, F. A.; Crisóstomo, S.; Paulino, E.; Martins, A. P. (International Journal of Clinical Pharmacy, 2018)
This commentary focuses on a description of solidarity initiatives developed by pharmacists in different practice areas. These are varied initiatives which contribute to improve the life of human beings in a wide range of formats with one common vector, the pharmacist’s involvement. Each of the initiatives described is related to the sustainable development goal it contributes to, whilst also referring to its link to international health policy documents, mostly issued by FIP. We expect this commentary further contributes to boost such initiatives in other parts of the world.